2014
DOI: 10.1016/j.juro.2014.03.040
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for 30-Day Perioperative Complications after Le Fort Colpocleisis

Abstract: Mortality and complication rates after colpocleisis are low with urinary tract infection being the most common postoperative complication. Concomitant sling placement does not increase 30-day complication rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 15 publications
2
19
0
1
Order By: Relevance
“…Zebede et al reported complication and mortality rates of 15.2% and 1.3%, respectively [15]. Catanzarite et al reported complications in 8.1% of 283 women who underwent Le Fort colpocleisis [16]. As in the current study, the most common complication was urinary tract infection, which was reported in 18 women (6.4%).…”
Section: Discussionsupporting
confidence: 59%
“…Zebede et al reported complication and mortality rates of 15.2% and 1.3%, respectively [15]. Catanzarite et al reported complications in 8.1% of 283 women who underwent Le Fort colpocleisis [16]. As in the current study, the most common complication was urinary tract infection, which was reported in 18 women (6.4%).…”
Section: Discussionsupporting
confidence: 59%
“…8 In another study, objective and subjective cure rates following colpocleisis in women over the age of 80 have been shown to be similar to those among younger women, 17 further promoting their safety and benefit in the older female population.…”
Section: Discussionmentioning
confidence: 91%
“…The advantages of the obliterative approach include the option for local anesthesia, shorter operative times, lower blood loss and faster recovery. 8 These benefits, in combination with extremely high success rates upwards of 90%, 912 makes this procedure ideally suited for frail older individuals who are not sexually active. The real-world use and outcomes of this obliterative procedure in comparison to the other reconstructive procedures, however, has yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…However, our findings are consistent with other studies that have shown that COPD in general is a risk factor for perioperative morbidity after urogynecologic and nonurogynecolgic surgery. For example, in a study published by Catanzarite et al, 15 COPD was significantly associated with 30-day perioperative complications in patients who underwent LeFort colpocleisis. Similarly, COPD was shown to increase the length of hospital stay in coronary artery bypass graft surgery patients 16 and was also found to be the only preoperative comorbid medical condition that increased the risk of readmission in a large cohort of patients who underwent outpatient thyroidectomy.…”
Section: Commentmentioning
confidence: 96%